RELASI AGAMA DAN SAINS DALAM STUDI ISLAM DI PTAI - Rasmianto, Rasmianto (ULUL ALBAB Jurnal Studi Islam, 2008)
It cannot be denied that religion and science play im portant roles in human life. The development of science in this modern world does not automatically reduce the influence of religion in human life, as predicted by the secularization theory. The fact that religion and science tend to be firmer interests many people, especially concerning the relation between them. Many perspectives and religious doctrines that seem in contradiction with the theory of modern science may arouse a conflict behveen religion and science. The case of execution to Galileo by the church in the nineteenth century and the long debate between the supporters of the Evolution and those of the Theory of Creation are the real proofs of the conflict between religion and science. To avoid the conflict, many people have tried to find the most appropriate model of relation. In the contemporary era, the "new flow" discussion of religion and science emerges. The discussion not only focuses on the level of discourse but also implementation. Many studies of integrativeinterconnection between religion and science in Islamic tertiary educational institutions indicate the efforts to match religion with science.